Narrowband Imaging for p16+ Unknown Primary Squamous Cell Carcinoma Prior to Transoral Robotic Surgery. (23rd June 2020) - Al‐Mulki, Kareem; Hamilton, James; Kaka, Azeem S.; Boyce, Brian J.; Baddour, H. Michael; El‐Deiry, Mark; Solares, C. Arturo; Magliocca, Kelly; Summers, Kelly; Aiken, Ashley; Saba, Nabil F.; Beitler, Jonathan J.; et al.
Abstract : Our purpose was to assess the potential utility of narrowband imaging (NBI) as a tool in diagnosing and treating unknown primary oropharyngeal squamous cell carcinoma (OPSCC) in patients prior to diagnostic resection with transoral robotic surgery (TORS). Between 2016 and March 2019, 29 patients with carcinoma of unknown primary meeting inclusion criteria were identified and treated with TORS. NBI was used preoperatively in 9 of 29 patients. A suspected tumor site was delineated by NBI in 8 of 9 patients (89%). Of the patients imaged with NBI, 8 of 9 (89%) patients had a pathologically confirmed tumor following TORS, corresponding to the same 8 suspected tumor sites identified with NBI. In contrast, a primary tumor was localized following TORS in 15 of 20 (75%) patients not evaluated with NBI. Thus, we see NBI as a potentially useful tool for the diagnosis and management of p16+ carcinoma of unknown primary. Level of Evidence : IIb